MULTI-TARGETS OPTIMIZATION DESIGN FOR MOVING CROSSBEAM OF MACHINE TOOL BASED ON ORTHOGONAL EXPERIMENTAL METHOD - JU JiaQuan; QIU ZiXue; CUI DeYou; REN Dong; SHANG AiKun (Jixie qiangdu)
In order to improve a machine moving beam’s comprehensive performances,which includes static and dynamic characteristics,it must have a reasonable beam ribs layout and structural properties. The crossbeam was simplified to get the mechanical vibration model,the maximum coupling deformation was solved by the theoretical calculation method. Using 3D software to establish the three-dimensional modeling of beam and ANSYS was used for static,modal analysis. Taking beam’s quality and the maximum coupling deformation,the maximum coupling stress,the first-order frequency as objective functions to judge the merits and drawbacks of crossbeam’s optimization,taking the crossbeam’s rib structure,the rib thickness,the angle of support stiffened plate as design variables for multi-objective optimization design. Orthogonal experimental method was used to design the orthogonal experiment with three levels and four factors. Using overall balance method to chose the optimal level,and then getting the best test program. The results show that: Theoretical analysis and simulation results are very similar. the beam with "井"type rib structure,rib thickness of 25 mm,the support stiffened plate tilted 55 ° design is the optimal solution.Compared with the original design,the beam deformation reduced by 7. 455% and the first-order frequency increased by 2. 956%,while the quality reduced by 473 kg. It shows that using the orthogonal experimental method to design reasonable levels and factors can achieve optimum results with fewer tests,and the orthogonal experimental method is valuable for engineering application.